Prosthetic rehabilitation of the dentate maxillectomy patient from a delayed surgical to an interim obturator: A clinical case report - Angleena Y Daniel; B Vinod (Wolters Kluwer Medknow Publications, 2015)
The surgical management of maxillary pathosis results in direct communication between the oral and nasal cavity, imposing problems such as nasal regurgitation, unintelligent speech, difficulty in deglutition and compromised esthetics. A restoration of these defects is not always possible surgically, but prosthetic rehabilitation is an established treatment modality. Early rehabilitation can improve the quality of life and reduce the psychological trauma caused by surgical excision. Surgical and interim obturators placed during the initial phase can improve the outcome of the definitive prosthesis. This article presents a case report of a patient with partial maxillectomy who has been rehabilitated with a delayed surgical and an interim obturator.